Pengaruh Surface Roughnes Pada Material AISI 1045 dan AISI 4140 Akibat Proses Pemesinan Bubut - Azhari, Wafiq; Aljufri, Aljufri; Rahman, Abdul; Putra, Reza; Akmal, Syarifah (Malikussaleh University, 2023)
Lathe machining is one type of conventional machine tool used for cutting/filling workpieces which is done by making an incision on the workpiece where the tool is moved translationally and parallel to the axis of the rotating workpiece. The result of the components of the turning process that is commonly done is surface roughness which is influenced by tool cutting angle, feeding speed, cutting speed, depth of cut. This study was conducted to determine how much influence the speed of feeding and depth of feeding on AISI 1045 steel and AISI 4140 steel materials used in shafts, conecting roads, gears with carbide chisels. With Vc=140 m/min, Vc=150 m/min, Vc=170 m/min, and Vc=180 m/min, and knowing the surface roughness of the workpiece using a carbide tool. From the results of research on AISI 1045 and AISI 4140 steel for cutting along 50 mm with engine speed 1200 rpm and cutting depth 0.3 mm, as well as the cutting speed used Vc=140 m/min, Vc=150 m/min, Vc=170 m/min and Vc=180 m/min and the initial cutting distance of 4 mm, the time needed is 1,125 minutes. For the surface roughness value of AISI 1045 steel material and AISI 4140 steel has four variations in lathe feeding speed in this study, which in each variation has a different surface roughness value, the smallest surface roughness value is AISI 4140 steel with a feeding speed vc = 180 m / min surface roughness value of 0.705 μm compared to AISI 1045 steel material. This is due to the greater the movement of the feeding speed of feeding, the smaller the value of the surface roughness of the material